Informe Agropecuario Mensual [Diciembre de 2016] - Carpaneto, Barbara Bettina; Lanzavecchia, Luis Agustin (Red de Información Agropecuaria Nacional (RIAN), 2024)
Incluye un informe anexo "Complemento"